ULTRA HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC DETERMINATION OF GENOTOXIC IMPURITIES IN FEBUXOSTAT DRUG SUBSTANCE AND PRODUCTS - N, Balaji; Sultana, Sayeeda (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: An efficient ultra-high performance liquid chromatographic (UHPLC or Infinity LC 1290) method has been developed and validated for the quantification of possible carcinogenic or genotoxic impurities in febuxostat drug substances and drug products at 18 µg/ml level. Methods: This method includes the conclusion of four potential genotoxic impurities in febuxostat. The mobile phase is trifluoroacetic acid, acetonitrile, and water with linear gradient elution. The UHPLC column used for the analysis was zorbax RRHD eclipse plus C18 with a length of100 mm, internal diameter of 2.1 mm, and particle size of 1.8 µ. Results: The limit of detection and limit of quantitation of the impurities are <0.1 (0.00001%) and 0.3 µg/ml (0.00003%) with respect to febuxostat test concentration of 1000 µg/ml, respectively. This method has been validated as per ICH guidelines Q2 (R1). Conclusion: A rapid, cost-effective infinity LC method was wonderfully established for quantitative analysis of possible genotoxic impurities of febuxostat drug substance and drug products. Keywords: Febuxostat, Genotoxic impurities, Ultra-high performance liquid chromatograph, Infinity-LC 1290, Validation